Safety and Efficacy of Autologous Cell Therapy in Critical Limb Ischemia: A Systematic Review. Issue 3 (March 2013) - Benoit, Eric; O'donnell, Thomas F.; Patel, Amit N.
Researchers have accumulated a decade of experience with autologous cell therapy in the treatment of critical limb ischemia (CLI). We conducted a systematic review of clinical trials in the literature to determine the safety and efficacy of cell therapy in CLI. We searched the literature for clinical trials of autologous cell therapy in CLI, including observational series of five or more patients to accrue a large pool of patients for safety analysis. Safety analysis included evaluation of death, cancer, unregulated angiogenesis, and procedural adverse events such as bleeding. Efficacy analysis included the clinical endpoints amputation and death as well as functional and surrogate endpoints. We identified 45 clinical trials, including seven RCTs, and 1, 272 patients who received cell therapy. The overall adverse event rate was low (4.2%). Cell therapy patients did not have a higher mortality rate than control patients and demonstrated no increase in cancer incidence when analyzed against population rates. With regard to efficacy, cell therapy patients had a significantly lower amputation rate than control patients (OR 0.36, p = 0.0004). Cell therapy also demonstrated efficacy in a variety of functional and surrogate outcomes. Clinical trials differed in the proportion of patients with risk factors for clinical outcomes, and these influenced rates of amputation and death. Cell therapy presents a favorable safety profile with a low adverse event rate and no increase in severe events such as mortality and cancer and treatment with cell therapy decreases the risk of amputation. Cell therapy has a positive benefit-to-risk ratio in CLI and may be a valuable treatment option, particularly for those challenging patients who cannot undergo arterial reconstruction.